Palm Sunday in central Mexico: among sellers, palms and syncretism - Jocelyn M. Briseño-Tellez; María Teresa Pulido Silva; Karen Bautista; Amairani García Mera; Omar Larios-Lozano; Berenice Nathaly López Gutiérrez; Yazmín Alejandra López López; Yesenia Mendoza Cruz; René Monzalvo; Daniela Ortega-Meza; Edith Carmina Sánchez Trejo; Zeltzin K. Zepeda-Hernández (BMC, 2023)
Abstract Background Domingo de Ramos, or Palm Sunday, is a traditional Christian religious event where devotees use ramos, which are bouquets currently elaborated from palm leaves and other natural elements. In various countries, it is assumed this use of biodiversity leads to the depletion of the species involved. However, other important aspects must be considered, including the role of the people who produce and sell these ramos, the associated symbolism that has been overlooked, as well as commercial aspects that have barely been documented. This ethnobotanical study evaluates the regional-scale cultural, biological and socioeconomic aspects associated with Domingo de Ramos in central Mexico from an emic perspective. Methods Ethnographic and commercial information was obtained through interviews with ramos sellers in 28 municipalities in the state of Hidalgo, Mexico. We specifically sought sociodemographic data regarding the interviewees, as well as information pertaining to the ramos themselves and the palms. These aspects were explored with all of the sellers. The free list method was used to describe the uses and key elements associated with the ramos. Results Although the ramos are used for religious purposes, they have eight different uses in the daily life of the sellers, the main one being "protection." They serve to protect families, crops and animals, as well as against several diseases. Likewise, they are considered valuable for diminishing strong storms. This belief in the protection conferred by the ramos preserves pre-Hispanic concepts and is combined with their use in blessing corresponding to Western beliefs. Ramos are made from 35 introduced and native plant species and comprise a base (made of palm, wheat or sotol), a "reliquia" (palm, rosemary, chamomile and laurel) and natural or artificial flowers. The ramos sellers are mostly adult women of indigenous origin and heads of family. Conclusions This study of Domingo de Ramos, carried out at a regional scale, highlights a syncretism that is reflected in both the symbolic importance of ramos palm and in the species used, as well as socioeconomic aspects that had not previously been identified in the study area and reflect the occurrence of complex relationships in non-timber forest products that remain little addressed.